KARATERISTIK PEMANFAATAN KAWASAN HUTAN DI DESA PARIGIMPU’U KECAMATAN PARIGI BARAT KABUPATEN PARIGI MOUTONG - Rifal, Ahmad; Rachman, Imran; Harijanto, Herman (Jurnal Warta Rimba, 2019)
Forest is one of the natural resources that has high economic, ecological and social value. The condition and condition of forests in Parigimpu'u Village in general is quite good at this time because the management and use of forest areas carried out by the village community in accordance with existing provisions This means that the use of forest areas carried out by local communities is the use of forest areas that are environmentally based, the form of utilization of forest areas carried out by local communities is by making community plantations. This research was conducted in May to June 2015. The research location was carried out in Parigimpu Village, Parigi District, West Parigi Mautong District, Central Sulawesi Province. This study aims to determine the characteristics and utilization of the Parigimpu Village community forest area. The attitude of the people of Parigimpu'u to obtain the benefits of the forest for their welfare in making smallholder plantations and based on data obtained in the field from 31 respondents in the village of Parigimpu'u, has various characteristics. From the results of the study the characteristics of the Parigimpu'u community do not have land until more than 3 hectares, most respondents have an average land of 1.5-2 hectares, the land is in the form of farm land and some are not yet cultivated and the use of Forest Areas in Parigimpu'u in use by the Community in the Village, as efforts to rehabilitate and conserve land, as well as diversification of agricultural products needed by the community, increasing community income that can be obtained from forests such as the supply of wood as building material, industrial raw materials, supply of fuel wood, improvement efforts environment that can benefit the surrounding community.Keyword: Characteristics, Utilization, Forest Area